Experimental investigation of Structural Behavior for Cross Laminated Timber (CLT) Wall-to-Floor Connection - Ceylan, Kygul; Girgin, Z. Canan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Cross-Laminated Timber (CLT) is an innovative industrial wood product, especially as a structural wall in order to meet the rigidity and strength requirements in multi-storey timber buildings. CLT members are assembled with metal connectors (angle bracket, joining plates, etc.) via nails, screws, dowels, etc. For energy-absorbing structural CLT connections, many experimental studies have been conducted on the effectiveness of the connections, especially for the earthquake prone regions. There is no scientific study in this context in Turkey yet. For this purpose; the performance of a full-scale CLT wall-to-floor specimen assembled with metal connection was experimentally investigated under axial tensile force due to bending moments of seismic loads. Domestic angle bracket, plates, and phosphate coated annular ring nails were used. All the displacements and strains were measured and collected during the test of the specimen, behavior of connection and the failure mode was observed. As a result, the back side deformation of CLT wall member was prevented with the plates for a longer period compared with no-plate case and the withdrawal resistance of from CLT floor increased through phosphate coated annular ring nails and extra three nails in the corner of angle bracket on the front side. Domestic metal connectors were used in the experiments to support the metal industry and the production with low cost. This study is a pioneering study in Turkiye on the experimental performance of CLT connections for the structural utilization. The results are promising, and the further experimental researches will continue for the most effective connection type.
Keywords: CLT wall-to-floor connection; CLT shear wall; cross laminated timber; earthquake resistant building design; phosphate coated annular ring nail; structural behavior; Architecture